Rancang Bangun Alat Pengepress Ban Elektrik untuk Merekatkan Ban Secara Otomatis - Flora, Musthafa Adam; Madyono, Madyono; Iman, Budi Nur (INOVTEK - Seri Elektro, 2021)
The tire patch tools that we often encounter on the side of the road mostly use traditional tire filling tools with the manual press method and heating on an iron plate. And use spiritus that is burned in the furnace to glue the patch. The process of patching tires takes a long time and sometimes the patcher has to make sure, whether the patch is glued or not. The problem is when opening the patch too quickly results in the patch not being completely glued. Likewise, when patching for too long will damage the tire surface. From this problem came the idea to make a tire patch tool with a display to find out the temperature when the tire patch tool works and also the length of time for the tire patch so that the tire patch automatically stops. This tool will be implemented on the surrounding tire patch. This study aims to determine the optimal temperature for tire filling to produce good fillings in a short time when compared to the usual tire filling time. In this research, we use a thermocouple sensor, Arduino Pro mini, organic light-emitting diode (oled), and a dc motor. The results of the filling with the specified temperature and time variations obtained good and bad results. The optimal temperature for tire patching in this test is at 70 ÌŠ C the temperature on the heating plate, with perfect patching results for 1 minute 50 seconds. The heat transfer rate on the plate is 37,763 watts and the heat transfer rate on the tires is 0.45 watts.